Single Charge Current in a Normal Mesoscopic Region Attached to Superconductor Leads via a Coupled Poisson Nonequilibrium Green Function Formalism - David Verrilli; F. P. Marin; Rafael Rangel (The Scientific World Journal)
We study the I-V characteristic of mesoscopic systems or quantum dot (QD) attached to a pair of superconducting leads. Interaction effects in the QD are considered through the charging energy of the QD; that is, the treatment of current transport under a voltage bias is performed within a coupled Poisson nonequilibrium Green function (PNEGF) formalism. We derive the expression for the current in full generality but consider only the regime where transport occurs only via a single particle current. We show for this case and for various charging energies values U0 and associated capacitances of the QD the effect on the I-V characteristic. Also the influence of the coupling constants on the I-V characteristic is investigated. Our approach puts forward a novel interpretation of experiments in the strong Coulomb regime.